PENGARUH MEDIA PEMBELAJARAN WORDWAAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII DI SMP ISLAM TAHFIZH DARUSSHOMAD 2 KALIJAGA TENGAH TA. 2024-2025 - A, Syarifa Nadia; Fikri, Ali; Sujono, Sujono (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to determine whether the wordwall method has an effect on student learning outcomes in Islamic religious education for seventh grade students at SMP Islam Tahfizh Darusshomad 2 Kalijaga Tengah. This study uses a quantitative approach with a quantitative experimental research design. This study was conducted at SMP Islam Tahfizh Darusshomad 2 Kalijaga Tengah. The sample for this study consisted of 30 seventh-grade students. Sampling was conducted using the purposive sampling method. The results of this study indicate that the wordwall method has an effect on student learning outcomes in Islamic Religious Education for seventh-grade students at SMP Islam Tahfizh Darusshomad 2 Kalijaga Tengah. This can be seen from the hypothesis test results which show a significance value (p-value) of 0.000 (smaller than 0.05), so that the alternative hypothesis is accepted and the null hypothesis is rejected. This means that there is a significant difference between the pretest and posttest scores of student learning outcomes after the application of the wordwall method. The difference in the average scores between the pretest and posttest of 6.100 points also shows a significant increase in student learning outcomes. This is reinforced by a t-value of -16.800, which indicates a very significant difference between the results before and after the treatment, with a total of 30 students as respondents.